2016
DOI: 10.17706/jsw.11.5.494-511
|View full text |Cite
|
Sign up to set email alerts
|

A New Three-Dimensional Chaotic System with Constant Exponent Spectrum: Analysis, Synchronization and Circuit Implementation

Abstract: Abstract:A new chaotic system with constant Lyapunov exponent spectrum is presented, two system parameters of which remain constant exponent characteristics. The basic dynamic properties of the new system are analyzed by Poincar section, Lyapunov exponent and dimension and the signal power spectrum. Based on the Lyapunov exponent spectrum, bifurcation diagrams and state variable amplitude with respect to system parameters show that the new system has two parameters with globally nonlinear modulation characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…based on the relation of the system parameter and the mathematical expression of the nonzero equilibrium point [52]. Thus, system (1) is degenerated to the normalized system about parameter k, as below ⎧ ⎨ ⎩ẋ…”
Section: Dynamics Analysis Of Amplitude and Position Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…based on the relation of the system parameter and the mathematical expression of the nonzero equilibrium point [52]. Thus, system (1) is degenerated to the normalized system about parameter k, as below ⎧ ⎨ ⎩ẋ…”
Section: Dynamics Analysis Of Amplitude and Position Modulationmentioning
confidence: 99%
“…These investigations only concern the robust chaos feature over a limited parameter range. Recently, we found that there exists robust chaos in the continuous chaotic system over infinite parameter range, and these parameters can regularly control the signal amplitude (which is called amplitude modulation for the convenience), yet the Lyapunov exponents keep invariable [50][51][52][53][54]. Therefore, it is a promising type of system in the practical application of image encryption, signal processing, synchronization and chaotic communication [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of chaos has benefited the exploration of the complex behavior, intrinsic nonlinear structure of natural system, and the construction of chaotic system, as well as practical applications such as secure communications and signal detection [5][6][7][8][9]. Robust chaotic system can usually provide signal-amplitude modulation by controlling one or some of the parameters in the dynamical equations yet keep the Lyapunov exponents and power spectral density invariable [10][11][12][13][14]. Therefore, it is a type of chaotic system with potential applications in synchronization, signal processing, image encryption, chaotic radar, and chaotic communication [10,12].…”
Section: Introductionmentioning
confidence: 99%